The B-G region genes of the chicken MHC are responsible for lethal graft-versus-host disease in newly hatched chickens - Plachý, J (Folia biologica, 1988)
Using the genetic model of Prague recombinant congenic lines of chickens we found that incompatibility in the B-G region of the major histocompatibility complex (MHC) causes very severe graft-versus-host reaction (GVHR)-associated haemolytic anaemia in newly hatched chickens. Unexpectedly, mild or no signs of this GVH disease are elicited when a recipient chick and an adult donor of lymphocytes are incompatible in the whole B haplotype (B-F/L + B-G regions). On the other hand, the B-G region incompatibility alone (as has been described previously) is not sufficient to produce any GVH splenomegaly in embryos at 14 days of incubation. However, GVH splenomegaly in the donor-recipient combinations with the difference in the whole B haplotype (B-F/L + B-G regions) is significantly greater than in those with the B-F/L region difference only. These results confirm that the B-G region genes of chicken MHC are also involved in the histocompatibility reactions. Furthermore, a new hypothetical model for the structure of the chicken MHC is discussed.
Keywords: Major Histocompatibility Complex; rekombinace genetická; testování histokompatibility; Recombination, Genetic; Chick Embryo; Splenomegaly; Histocompatibility Testing; splenomegalie; Haplotypes; kuřecí embryo; nemoc štěpu proti hostiteli; kur domácí; Chickens; zvířata; Graft vs Host Disease; autoimunitní hemolytická anemie; haplotypy; hlavní histokompatibilní komplex; Anemia, Hemolytic, Autoimmune; Animals